TINGKAT KESUBURAN PERAIRAN KOLAM AGROWISATA UIR DITINJAU DARI KONSENTRASI KLOROFIL-a PHYTOPLANKTON DI KECAMATAN SIAK HULUKABUPATEN KAMPARPROVINSI RIAU - Muhammad Hasby (DINAMIKA PERTANIAN, 2017)
This study aims to determine the level of water fertility in the UIR Agro-tourism pond in the District of Siak Hulu, Kampar Regency, Riau Province based on the concentration of chlorophyll-a phytoplankton. The study was carried out for 6 months in the Agro-tourism pond in Riau Islamic University. Analysis of water fertility in situ and ex-situ. The parameters measured were chlorophyll-a phytoplankton concentration and water quality. The method used is a case study (survey). The treatment in this study was 3 replications in one week on the clock and the same pool sequence. The results showed that the pond fertility rate of UIR Agro-tourism was quite productive, namely chlorophyll-a concentration of 1-20 µg / l with an abundance of phytoplankton of 104 cells / l.